Degree of maturity in project management in software development companies - Merlo, Geovane Moraes; Bosi, Mirela Guedes (Brazilian Journal of Production Engineering, 2024)
Increased accessibility to technology results in increasingly competitive markets for technology-based companies. This change of scenery requires a constant search for excellence in management and therefore in project management. In this search, it is necessary to determine the current maturity level to identify central points of improvement. The objective of this study was to analyze the degree of maturity in project management in two small software development companies in Espírito Santo. Therefore, it was necessary to select an appropriate model, characterize the project management, and classify the level of maturity. Based on the literature review about the maturity models, a model adapted from OPM3 was selected and applied for the diagnosis of project management. In addition, interviews and direct observation were conducted to characterize the projects of the companies and identify the degree of maturity in project management. The results indicated that the maturity levels of both companies surveyed were below the ideal, although positive interferences were observed by companies that are customers of the companies surveyed, regarding the internal processes of software construction.